Moving with the Trend: the Impact of Digital Technologies on Journalism Practice in Imo State, Nigeria - Пейшенс Ай; Філомена Еффіонг Уморен; Фабіан Окалла; Кізіто Нзубе Алаекве; Крістіан Чадді Одуені; Емека Вільямс Етумну (Cхід)
The integration of digital technology into the field of journalism in Nigeria has en-gendered both obstacles and prospects, hence fostering advancements in the in-dustry. As a result of this, the study assessed the impact of digital technologies application on mainstream journalism practice among journalists in Imo State. The research was grounded in the theoretical frameworks of technological determinism and new media theory. The study employed a survey research approach, utilising a census principle to sample a population of 200 registered journalists. Questionnaire was the instrument for data collection. Results showed that majority of the respond-ents have access to digital technologies in the discharge of their duties to a large extent at 66% and they use digital technologies often. The respondents have a posi-tive perception towards the application of digital technologies in journalism practice with the believe that digital technology is a blessing to journalism profession at an average mean of 3.6. Result also revealed that digital/computer illiteracy, lack of the requisite knowledge to operate digital technologies gadgets, high cost of acquiring digital technologies gadgets by the media organisation etc. are the challenges faced by the respondents while using digital technologies to carry out their reportorial du-ties at an average mean of 3.7. The result further revealed that digital technologies application in journalism practice has influenced journalism by improving the profes-sional process of news gathering, production and dissemination at an average mean of 3.6. The study concluded that digital technology has improved the professional process of news gathering, production and dissemination, thus, has significantly influenced journalism practice. The study recommended for the acceptance of digital switchover by media organisations and its embrace among the journalists.